Analisis Harga dan Kualitas Layanan Vendor dalam Keputusan Pembelian Barang di Harris Resort Barelang Batam - fina frisca oktarinda; Yuke Permata Lisna; Jefriko Jefriko (Departemen Pariwisata Universitas Negeri Padang, 2026)
This study aims to analyze the consideration of price and vendor service quality in purchasing decisions at Harris Resort Barelang Batam. The study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with four informants, namely the Purchasing Manager, Receiving Staff, Food and Beverage Product Supervisor, and Cost Control Staff, supported by observation and documentation. Data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing, while data validity was assessed through source triangulation. The findings indicate that price serves as an initial consideration in vendor selection, particularly in terms of affordability and conformity with the hotel's budget. However, purchasing decisions are not determined solely by price, but also by product quality and vendor service quality. Reliability in ensuring timely delivery and vendor responsiveness are the most influential factors in supporting smooth hotel operations, while assurance and empathy contribute to the development of long-term cooperative relationships. Purchasing decisions are also based on the suitability of goods for operational needs, product benefits, the appropriateness of vendor selection, and previous satisfaction experiences. Therefore, purchasing decisions at Harris Resort Barelang Batam result from an integrated consideration of price, vendor service quality, and operational needs, thereby supporting the effectiveness of the hotel's procurement process.